2011
DOI: 10.1113/jphysiol.2010.202184
|View full text |Cite
|
Sign up to set email alerts
|

Hippocampal microcircuit dynamics probed using optical imaging approaches

Abstract: Mammalian cortical structures are endowed with the capacity for plasticity, which emerges from a combination of the dynamics of circuit connectivity and function, and the intrinsic function of the neurons within the circuit. However, this capacity is accompanied by a significant risk: the capability to generate seizure discharges is also a property of all mammalian cortices. How do cortical circuits reconcile the requirement to maintain plasticity, but at the same time control seizure initiation? These issues … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
41
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(43 citation statements)
references
References 44 publications
(95 reference statements)
2
41
0
Order By: Relevance
“…As a complement to our studies of cortical interneurons, we tested the functional consequence of selective deletion of Na v 1.1 in CA1 horizontal stratum oriens lacunosum-moleculare (O-LM) cells. O-LM cells are critical for regulation of action potential firing of CA1 pyramidal cells and thereby exert important inhibitory control of circuit function and prevent epilepsy (Maccaferri and McBain, 1995;Pouille and Scanziani, 2004;Coulter et al, 2011). These cells represent a distinct subtype of interneurons that express both SST and PV (Maccaferri et al, 2000;Ferraguti et al, 2004), and their excitability was shown to be reduced in Dravet syndrome mice with global deletion of Na v 1.1 (Rubinstein et al, 2014).…”
Section: Deficits Of Excitability and Synaptic Amplification In Hippomentioning
confidence: 99%
“…As a complement to our studies of cortical interneurons, we tested the functional consequence of selective deletion of Na v 1.1 in CA1 horizontal stratum oriens lacunosum-moleculare (O-LM) cells. O-LM cells are critical for regulation of action potential firing of CA1 pyramidal cells and thereby exert important inhibitory control of circuit function and prevent epilepsy (Maccaferri and McBain, 1995;Pouille and Scanziani, 2004;Coulter et al, 2011). These cells represent a distinct subtype of interneurons that express both SST and PV (Maccaferri et al, 2000;Ferraguti et al, 2004), and their excitability was shown to be reduced in Dravet syndrome mice with global deletion of Na v 1.1 (Rubinstein et al, 2014).…”
Section: Deficits Of Excitability and Synaptic Amplification In Hippomentioning
confidence: 99%
“…A combination of single-cell electrophysiology and fast imaging techniques (Carlson and Coulter 2008;Coulter et al 2011) can now allow us to probe the role of neuromodulators in altering neural activity patterns and intercellular synchronization (Dzirasa et al 2010;Fernandez de Sevilla et al 2006;Puig et al 2010). Thus it is important to use this combination of these techniques to determine emergent neural network dynamics and their modulation on cell-to-cell and network levels.…”
mentioning
confidence: 99%
“…During cortical circuit development in the mammalian brain, functional microcircuits form from groups of excitatory neurons receiving similar sensory information (33)(34)(35)(36)(37). The emergence of functional populations is not limited to the sensory cortex but also occurs in other subcortical areas during normal development or learning, a phenomenon that is increasingly acknowledged as a general characteristic of neural coding in the mammalian brain (38)(39)(40)(41)(42)(43). Presumably, changes in synaptic strength and/or modification of neuronal connectivity underlie this process, but we lack a systematic understanding of circuit rearrangement at a multineuron level.…”
Section: Discussionmentioning
confidence: 99%